The Challenge of Preserving and Expanding Affordable Health Care in Maine - Wolf, Wendy (Maine Policy Review, 2003)
Maine’s health care system is in crisis. The state’s health care expenditures represent the third highest percentage of Gross Domestic Product in the nation; state health care spending is projected to top 11 billion per year, or 8,291 per person per year, over the next seven years; businesses in Maine pay 12-23% more for coverage than the national and New England state averages; and, the state’s uninsured and vulnerable populations continue to grow. In this article, Wendy Wolf charts the rising cost of health care in Maine and the implications of these costs for all Mainers. In turn, she looks at each of the drivers of cost and calls for a comprehensive approach to solving the crisis. Only when all of the players agree to work together and, more importantly, to make changes will we be able to change directions.